GOLD Classifications, COPD Hospitalization, and All-Cause Mortality in Chronic Obstructive Pulmonary Disease: The HUNT Study - Bhatta,Laxmi; Leivseth,Linda; Mai,Xiao-Mei; Henriksen,Anne Hildur; Carslake,David; Chen,Yue; Langhammer,Arnulf; Brumpton,Ben Michael (International Journal of Chronic Obstructive Pulmonary Disease, 2020)
Laxmi Bhatta,1 Linda Leivseth,2 Xiao-Mei Mai,1 Anne Hildur Henriksen,3,4 David Carslake,5,6 Yue Chen,7 Arnulf Langhammer,8,* Ben Michael Brumpton4,5,9,* 1Department of Public Health and Nursing, NTNU Norwegian University of Science and Technology, Trondheim, Norway; 2Centre for Clinical Documentation and Evaluation (SKDE), Northern Norway Regional Health Authority, Tromsø, Norway; 3Department of Circulation and Medical Imaging, NTNU Norwegian University of Science and Technology, Trondheim, Norway; 4Clinic of Thoracic and Occupational Medicine, St. Olavs Hospital, Trondheim University Hospital, Trondheim, Norway; 5Medical Research Council Integrative Epidemiology Unit, Department of Population Health Sciences, Bristol Medical School, University of Bristol, Bristol, UK; 6Population Health Sciences, University of Bristol, Bristol, UK; 7School of Epidemiology and Public Health, University of Ottawa, Ottawa, Canada; 8HUNT Research Centre, Department of Public Health and Nursing, NTNU Norwegian University of Science and Technology, Levanger, Norway; 9K.G. Jebsen Center for Genetic Epidemiology, Department of Public Health and Nursing, NTNU Norwegian University of Science and Technology, Trondheim, Norway*These authors contributed equally to this workCorrespondence: Laxmi BhattaDepartment of Public Health and Nursing, Faculty of Medicine and Health Sciences, NTNU Norwegian University of Science and Technology, P.O. Box 8905, MTFS, Trondheim NO-7491, NorwayEmail laxmi.bhatta@ntnu.noPurpose: The Global Initiative for Chronic Obstructive Lung Disease (GOLD) has published three classifications of COPD from 2007 to 2017. No studies have investigated the ability of these classifications to predict COPD-related hospitalizations. We aimed to compare the discrimination ability of the GOLD 2007, 2011, and 2017 classifications to predict COPD hospitalization and all-cause mortality.Patients and Methods: We followed 1300 participants with COPD aged ≥ 40 years who participated in the HUNT Study (1995– 1997) through to December 31, ...